2017
DOI: 10.21873/anticanres.12057
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Lysosomal System of Cervical Cancer Cells Induced by Emodin Action

Abstract: Emodin induces degradation processes and promotes the death of tumor cells through a mechanism that occurs with clear involvement of the lysosomal compartment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
(47 reference statements)
1
7
0
Order By: Relevance
“…In 2017, Trybus et al . found that emodin could cause significant changes in the lysosomal compartment of HeLa cells, which manifested as an increase in the number of lysosomes and an increase in autophagic vacuoles, leading to lysosomal membrane damage 198 . Furthermore, a recent study reported that emodin is a photosensitizer in combination with photodynamic therapy that significantly increased cytotoxicity to SiHa, CaSki, and HaCaT cells, which was associated with increased ROS production, caspase-3 activity, and autophagy 199 .…”
Section: Anticancer Effects Of Emodinmentioning
confidence: 99%
“…In 2017, Trybus et al . found that emodin could cause significant changes in the lysosomal compartment of HeLa cells, which manifested as an increase in the number of lysosomes and an increase in autophagic vacuoles, leading to lysosomal membrane damage 198 . Furthermore, a recent study reported that emodin is a photosensitizer in combination with photodynamic therapy that significantly increased cytotoxicity to SiHa, CaSki, and HaCaT cells, which was associated with increased ROS production, caspase-3 activity, and autophagy 199 .…”
Section: Anticancer Effects Of Emodinmentioning
confidence: 99%
“…Emodin applied to HeLa cells in the concentration range of 1–100 μM changed the lysosomal compartment, increased autophagic vacuoles, and lysosomal hydrolase activity significantly. Increasing lysosomal membrane damage at increasing concentrations exhibited cytotoxic activity against lysosomes [ 151 ]. In their later study, Trybus et al again discussed the apoptotic mechanism of emodin in HeLa cells in the concentration range of 1–100 μM.…”
Section: Anticancer Activity Of Emodinmentioning
confidence: 99%
“…A recent study revealed that emodin at 20 or 40 μM induced apoptosis in human colon cancer cell lines (HCT116 and LOVO) through a ROS accumulation-mediated autophagy activation [ 99 ]. Emodin (1–100 μM) also facilitated lysosomal-dependent autophagosome degradation via increasing the number of lysosomes and autophagic vacuoles as well as enhancing the activity of lysosomal hydrolases in cervical cancer cells (HeLa), and thus induced cell death [ 100 ]. Furthermore, necroptosis is another general mechanism of cell death independent from apoptosis.…”
Section: Pharmacological Effects Of Emodinmentioning
confidence: 99%